Adoption of customer centered service in Public University: a case study in Malaysia - NorHapiza, Mohd Ariffin; Norfarizan, Mohd Daud (Springer Verlag, 2018)
The Information and Communication Technology (ICT) represents a basis for the development of academic institution in public sector. Thus, there is a huge emerging from the traditional academic institution into technological environment based. ICT implementations indirectly will represent the major changes of the business processes. In term of providing the best ICT facilities and infrastructure, there are often issues about service delivering, customer expectation, utilization of infrastructure, knowledge sharing and matters regarding ICT services. Therefore, this study was conducted to analyze the adoption of customer centered service for ICT services in Malaysian public university. There are two main objectives of this study which first, to identify the current status of customer centered service for ICT services and second, to identify the impact of adoption of customer centered service for ICT services. About 10 public universities in Malaysia involved in this study. Interview and questionnaires were used for collecting data. The findings showed that 80% of public universities in Malaysia have adopted customer centered services to facilitate the ICT services and facilities in their universities and this study revealed about the positive impact of customer centered service to the ICT services. Suggestions as to what future research should indicate are also discussed.